Sociological Analysis of the Sense of Social Belonging among Women in the Urban Community of Arak - Bayati, Zahra; Mashhadi, Jila; Yarmohammadtousky, Maryam; Seyyedi, Faranak (Psychology of Woman Journal, 2025)
Objective: The objective of this study was to investigate the level of social belonging among women in the urban community of Arak and to examine the factors influencing this belonging. Methods and Materials: This research employed a descriptive, cross-sectional survey method. The study sample consisted of 418 women from Arak, selected using stratified sampling based on population size. Data collection was conducted through a structured questionnaire, which was validated using content validity and the Content Validity Ratio (CVR) method, as well as Cronbach’s alpha to ensure reliability. The questionnaire assessed four main dimensions of social belonging: attachment to symbols and norms, social trust, extreme individualism, and socioeconomic status. Data analysis involved factor analysis and structural equation modeling using Smart PLS software. Findings: The results revealed that most women in the sample reported moderate levels of social belonging, with 61.6% indicating a moderate sense of belonging, 22.6% a low sense, and 15.8% a high sense. About 42% of women expressed dissatisfaction with urban symbols and norms, while 35% had a positive view of social trust in Arak. Approximately 34% of respondents prioritized personal interests over group interests, indicating a significant presence of extreme individualism. Factor analysis confirmed that social trust, attachment to symbols, and overall social belonging accounted for over 43% of the variance in related variables, and the confirmatory factor analysis validated the proposed model of social belonging among women in Arak. Conclusion: The study concluded that social belonging is crucial for urban quality of life and is influenced by emotional and social factors such as trust and attachment to the environment. The findings aligned with Durkheim’s and Giddens’ theories, emphasizing the importance of emotional bonds and the interconnection between social structures and individual actions.